Role Of Independent Commissioner In Moderating The Impact Of Banking Corporation Size Toward Audit Delay - Merawati, Endang Etty; Djadang, Syahril (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2023)
Abstract : In 2014, some Issuers in Indonesian Stock Exchange have not submitted their midterm financial statement and in fact some of them got sanctioned. In regard thereto, this study aim to analyse the effect of firm’s size toward audit delay moderated by Independent Commissioners on banks listed on the Indonesian Stock Exchange . This research used purposive sampling method, from total 41 banks listed on the Indonesian Stock Exchange on 2011-2014, only 28 banks meet the criteria. This research method uses a quantitative approach. The result of the study shows that firm,s size, and Independent Commissioners has partially significant influence on audit delay. However, Independent Commissioners shows a non significant effect as a moderation of Companies’ Size toward Audit Delay. The contribution of this study is that Independent Commissioner have optimal role in carrying out internal controls to avoid delays in submission of audited financial statement in the banking sector Keywords: companies’ size, independent commissioners, audit delay, banking sector